Rootstock‐conferred traits affect the water use efficiency of fruit production in Shiraz. (27th March 2022) - Edwards, E.J.; Betts, A.; Clingeleffer, P.R.; Walker, R.R.
Abstract: Background and Aims: Rootstock type can lead to differences in scion canopy growth and fruit yield by conferring specific traits to the scion. Conferred traits may interact to alter the relationship between vine water use and fruit yield, providing a mechanism whereby rootstocks could be used to improve the water use efficiency of fruit production. This study aimed to determine whether rootstock conferred vigour and crop water use index (yield per unit water transpired) were linked. Methods and Results: Seven rootstock genotypes, grafted with Shiraz, in a trial established over 20 years previously, were assessed over four seasons for vigour, yield and leaf physiology, and over three seasons for whole vine transpiration using sapflow sensors. There were consistent differences in rootstock conferred traits, with yield being affected to a lesser extent than vigour or vine water use. Conclusions: The water use efficiency of fruit production was improved for Shiraz on low vigour conferring rootstocks, due to a combination of rootstock conferred effects on scion vigour, leaf gas exchange, whole vine transpiration and yield. Significance of the Study: The study has demonstrated that rootstock conferred traits can alter the crop water use index of the scion in a mature vineyard. Consequently, accurately matching irrigation application with vigour and leaf physiology traits of the chosen rootstock has the potential to be used as a tool to optimise vineyard water use efficiency, even in fully irrigated vineyards.